Microbial Desalination Cell (MDC) in the Presence of Activated Carbon - Aidan, Ahmed (2014)
This report studies the performance of a Microbial Desalination Cell (MDC) in the presence ofactivated carbon in both the cathode and anode chambers. The large surface area of the activatedcarbon provides surface for bacterial growth, thereby leading to the formation of a stronger microbialculture through the formation of a biofilm. An MDC of 60 ml total capacity is used to achieve60 percent desalination within 20 hours. In addition, a maximum mean voltage of 105 mV and apower density of 1.546 mW/m2 are obtained when a 3.2-k resistor was used. The results of ourexperiments suggest that the addition of activated carbon to the anodic and cathodic chambersimproves MDC performance. This technology has the potential to be used to integrate a wastewater treatment plant and a desalination facility.